2022
DOI: 10.3389/fphar.2022.1017830
|View full text |Cite
|
Sign up to set email alerts
|

Cell metabolomics study on the anticancer effects of Ophiopogon japonicus against lung cancer cells using UHPLC/Q-TOF-MS analysis

Abstract: Ophiopogon japonicus (OJ) is a traditional Chinese herbal medicine that has been used for thousands of years. Recently, the anticancer effects of OJ have been reported in multiple types of cancer, particularly in lung cancer. However, the underlying mechanisms remain unclear. In present study, the effects of OJ against NCI-H1299 human lung cancer cells were investigated, and the underlying mechanisms were explored using ultra-high-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…[14] In addition, another study found that Ophiopogon japonicus and Salvia miltiorrhiza may have a delayed effect on the development of pulmonary fibrosis by activating superoxide dismutase, inhibiting the scavenging of free radicals, improving the balance between oxidation and antioxidation, reducing cell membrane damage in lung tissue, and weakening the inflammatory response. [15] Fibrosis is scarring and tissue sclerosis caused by excessive deposition of extracellular matrix proteins by myofibroblasts in response to chronic inflammation. [16] A variety of noxious stimuli (including toxins, infectious agents, autoimmune responses, and mechanical stress) can induce fibroblast responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] In addition, another study found that Ophiopogon japonicus and Salvia miltiorrhiza may have a delayed effect on the development of pulmonary fibrosis by activating superoxide dismutase, inhibiting the scavenging of free radicals, improving the balance between oxidation and antioxidation, reducing cell membrane damage in lung tissue, and weakening the inflammatory response. [15] Fibrosis is scarring and tissue sclerosis caused by excessive deposition of extracellular matrix proteins by myofibroblasts in response to chronic inflammation. [16] A variety of noxious stimuli (including toxins, infectious agents, autoimmune responses, and mechanical stress) can induce fibroblast responses.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] In addition, another study found that Ophiopogon japonicus and Salvia miltiorrhiza may have a delayed effect on the development of pulmonary fibrosis by activating superoxide dismutase, inhibiting the scavenging of free radicals, improving the balance between oxidation and antioxidation, reducing cell membrane damage in lung tissue, and weakening the inflammatory response. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%